Reply to Berlanga et al. (DOI 10.1515/cclm-2014-0420) - Joannes F.M. Jacobs; Rein M.J. Hoedemakers; Henk te Velthuis (Clinical Chemistry and Laboratory Medicine (CCLM), 2014)
Albumin measurements in serum have important diagnostic and prognostic roles. However, non-standardized measurement procedures are still used in medical laboratories. An agreed approach for the implementation of metrological traceability to the International System of Units (SI) of serum albumin measurements is lacking and the use of non-selective assays in medical laboratories is still predominant. This paper provides an analysis of the current status of serum albumin measurements, including discussion on how to improve standardization and highlighting some important aspects that still require adequate solutions, such as the abandonment by medical laboratories of non-selective bromocresol green methods based on risk of clinical harm. The discussion also includes considerations about the analytical performance specifications that should be fulfilled when using serum albumin measurements for patient management decisions.